2022
DOI: 10.3390/pharmaceutics14122566
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of High-Molar-Activity Samarium-153 for Targeted Radionuclide Therapy with [153Sm]Sm-DOTA-TATE

Abstract: Samarium-153 is a promising theranostic radionuclide, but low molar activities (Am) resulting from its current production route render it unsuitable for targeted radionuclide therapy (TRNT). Recent efforts combining neutron activation of 152Sm in the SCK CEN BR2 reactor with mass separation at CERN/MEDICIS yielded high-Am 153Sm. In this proof-of-concept study, we further evaluated the potential of high-Am 153Sm for TRNT by radiolabeling to DOTA-TATE, a well-established carrier molecule binding the somatostatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A promising strategy to overcome treatment-induced resistance involves the use of higher-energy radioisotopes for radiolabeling DOTA-TATE, including other βor αemitters. One such approach is the radiolabeling of DOTA-TATE with Samarium-153 ( 153 Sm, 153 Sm-DOTA-TATE), a β-emitter that emits electrons with higher energy than 177 Lu and, therefore, with larger range in the tumors [34]. 153 Sm also emits γ-particles, making this radioelement also suitable for SPECT imaging.…”
Section: Dota-tate-based Radiotracermentioning
confidence: 99%
See 1 more Smart Citation
“…A promising strategy to overcome treatment-induced resistance involves the use of higher-energy radioisotopes for radiolabeling DOTA-TATE, including other βor αemitters. One such approach is the radiolabeling of DOTA-TATE with Samarium-153 ( 153 Sm, 153 Sm-DOTA-TATE), a β-emitter that emits electrons with higher energy than 177 Lu and, therefore, with larger range in the tumors [34]. 153 Sm also emits γ-particles, making this radioelement also suitable for SPECT imaging.…”
Section: Dota-tate-based Radiotracermentioning
confidence: 99%
“…In vitro studies conducted on gastroenteropancreatic neuroendocrine tumor cell lines demonstrated a high uptake and internalization of the radiotracer. Moreover, biodistribution studies in mice with gastroenteropancreatic neuroendocrine tumor xenografts showed rapid clearance and strong tumor uptake of the radiotracer [34]. However, the therapeutic potential of 153 Sm-DOTA-TATE is yet to be fully evaluated and compared with that of 177 Lu-DOTA-TATE.…”
Section: Dota-tate-based Radiotracermentioning
confidence: 99%
“…Meanwhile, the beta-emitting nature of 153 Sm (with a maximal energy of 0.81 MeV and a short half-life of 1.9 days) ensures targeted eradication of sub-centimeter-sized cancer cells, minimizing collateral damage to neighbouring healthy tissue. 18 This approach capitalizes on the synergistic benefits of each component, creating a versatile platform for dual-targeted therapy and non-invasive monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…One of the focal points of this Special Issue is the exploration of TRT using high-molar-activity samarium-153, produced by combining the neutron activation of samarium-152 and mass separation of the resulting samarium-153 from carrier samarium-152. Vermeulen et al from the Belgian Nuclear research center have successfully labeled DOTATATE with 153 Sm, resulting in [ 153 Sm]Sm-DOTATATE, and successfully evaluated the compound to target somatostatin receptors overexpressed in neuroendocrine tumors [ 1 ]. This proof-of-concept study shows the potential of mass-separated samarium-153 and could open doors towards the wider application of mass separation in medical isotope production.…”
mentioning
confidence: 99%